Global and Domestic Challenges Confronting Buddhist Institutions in Japan - John Nelson (Journal of Global Buddhism, 2015)
With the rise of globalization in the past twenty years, the positioning of religious belief and activity worldwide has become increasingly complicated due to new information technologies, immigration flows, corporate restructuring and transnational finance. This paper identifies five factors that not only characterize late modern societies but also create conditions to which religions must adapt, or ignore at their peril. Using Buddhist temples, priests, and their surrounding communities in Japan as case studies, the paper traces how social forces such as 1) a “crisis of orientation,” 2) corporate and bureaucratic restructuring, 3) consumer culture, 4) individualization within a “risk” society, and 5) experimental approaches to spirituality impact religious practice and institutions. Without a perspective that incorporates the global into the local (but still acknowledges the power of individual agency), our analysis of religious activities remains parochial and sociocentric.